A relational study on consumer promotion, price Perception, service quality perception and brand loyalty in the context of telecommunication industry in Bangladesh - Sultana, Nasrin (BRAC University, 2014)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2013.